Webcasting Videoconferences Over IP: A Synchronous Communication Experiment - Locatis, Craig (American Medical Informatics Association, 2003)
A multipoint videoconference was webcast live to an audience who could communicate with conference panelists and each other via chat. The videoconference, webcast, and chat were done entirely over the Internet. Seven panelists at four conference sites that had Internet2 connectivity and were located in different time zones within the continental United States discussed the topic of “Evaluating Health Professions Education and Information Resources on the Web.” This discussion was broadcast to individuals and groups at various U.S. locations who had expressed an interest in the topic and had sufficient connectivity for receiving the video stream. Webcast recipients could log on a chat server and type questions and comments to the panelists and other viewers. The experiment’s rationale, procedures, and outcomes are described, and issues associated with the use of the technologies are identified.